Tratamiento de la deformidad facial causada por la hiperplasia condilar: relato de caso - Monnazzi, Marcelo Silva [UNESP] (2010)
The condylar hyperplasia is an acquired development anomaly, rare, characterized by an excessive and progressive growing, affecting neck, condilar head, body and the mandible bough, provoking an important facial asymmetry. In the article we present a case of male patient, 22-years-old, reclaiming of painful sintomatology in the region of temporomandibular joint and severe facial asymmetry. It was instituted an orthodontic-surgical treatment by means of orthognathic combined surgery and high condilectomy. After six years of post-surgical controlling, the patient is now in a good shape, without recurrence of facial asymmetry and condylar hyperplasia.